Enhanced thermoelectric performance in polycrystalline N-type Pr-doped SnSe by hot forging. (15th May 2020) - Li, Shan; Zhang, Fanghao; Chen, Chen; Li, Xiaofang; Cao, Feng; Sui, Jiehe; Liu, Xingjun; Ren, Zhifeng; Zhang, Qian
Abstract: SnSe has attracted significant attention for use in thermoelectric devices due to its reported ultrahigh figure-of-merit ZT in both p- and n-type single crystals, which inspired us to explore the thermoelectric properties of SnSe polycrystals for potential large-scale applications. Here, n-type Sn1- x Pr x Se polycrystals are prepared by ball milling and hot pressing. A maximum ZT value of ~0.7 at 773 K is achieved in Sn0.97 Pr0.03 Se due to the enhanced electron concentration and electrical conductivity resulting from Pr doping at the Sn site. Through hot forging for a higher degree of orientation, a lowered thermal conductivity is obtained along the hot-pressing direction, contributing to an enhanced ZT value of ~0.9 at 773 K in this direction. This study paves a new way for optimization of n-type SnSe by cation-site lanthanide doping. Graphical abstract: Image, graphical abstract